2000
DOI: 10.1002/1521-3927(20000901)21:14<983::aid-marc983>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

A generalized method to calculate diffusion rates in polydisperse systems. Further results on Rouse dynamics in the concentrated regime

Abstract: Experiments designed to thoroughly test a recently proposedgeneralized method to calculate diffusion rates in polydisperse systems have been carried out. Polydisperse polystyrene (PS) samples were allowed to diffuse in a poly(phenylene oxide) (PPO) matrix. Designed blends were made from anionically polymerized PS with molecular weights which cover most of the ranges where Rouse dynamics control the diffusion processes. The diffusion temperatures range from (Tg – 1 K) to (Tg + 105 K), causing the monomeric fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
(16 reference statements)
2
5
0
Order By: Relevance
“…This is demonstrated by the fact that the physical diffusion model used for calculations and simulations in this work has also been used with success for the study of liquid−liquid diffusion experiments using the same polymer pair at temperatures above the PPO-rich-layer T g . ,, The diffusion process is characterized by the transport of PS from the original PS-rich thin layer into layers that are richer in PPO, and the PPO transport is always realized toward layers with lower local T g values. The whole dynamics for the faster-diffusing species (PS) is Rouse-type, as shown in earlier works. ,, For the entire chemical composition range used, the monomeric friction factor for the PS species follows the WLF dependence on temperature, through the parameter ( T − T g ) …”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This is demonstrated by the fact that the physical diffusion model used for calculations and simulations in this work has also been used with success for the study of liquid−liquid diffusion experiments using the same polymer pair at temperatures above the PPO-rich-layer T g . ,, The diffusion process is characterized by the transport of PS from the original PS-rich thin layer into layers that are richer in PPO, and the PPO transport is always realized toward layers with lower local T g values. The whole dynamics for the faster-diffusing species (PS) is Rouse-type, as shown in earlier works. ,, For the entire chemical composition range used, the monomeric friction factor for the PS species follows the WLF dependence on temperature, through the parameter ( T − T g ) …”
Section: Resultssupporting
confidence: 81%
“…As expected from the physical diffusion model, the highest slope, associated with a higher T g , is located next to the glassy matrix, and a gradually decreasing slope shows the influence of the rapidly changing T g profile along the diffusion path. For experiments conducted 1 K below the glassy matrix T g value in earlier work, it has been shown that when the local T g changes by about 80 K along the diffusion path, the PS monomeric friction coefficient changes by about 7 orders of magnitude, 33 thus justifying the chemical composition profile shape shown in Figure 2. Similar agreement between convoluted model calculations and experimental Raman data was obtained for all of the diffusion experiments of types A-C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation could be accounted for in the framework of reptation considering the temperature dependence of the friction coefficient of eq that was assumed to be constant in eq . Indeed, several authors have clearly pointed out the strong ζ-dependence on temperature , that is unfortunately often ignored . This ζ temperature dependence that applies for reptation should also apply for “sideways motions” or “segmental rather to macromolecular mobility” which are likely to contribute to interface healing after melting explosion.…”
Section: Results and Data Analysismentioning
confidence: 99%
“…The error bars hold for the extend of the data dispersion between the highest and the lowest experimental values are not always visible at the graph scale. All of these data have been analyzed by means of statistical tests , in order to determine the regression line and the corresponding slopes reported on Figure c. A classical Student’s t test was used to check whether the slope of the regression line differs significantly from zero, whereas Snedecor’s tests enabled to confirm whether the two regression lines differ significantly from one another.…”
Section: Resultsmentioning
confidence: 99%